Implementasi Marketing Mix di PT.Adira Finance Cabang Meulaboh - Putri Moyna Ikhsani; Chairiyaton Chairiyaton; Mardaleta Mardaleta; Cut Mega Putri (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to analyze how the implementation of the marketing mix (4P) at PT Adira Finance, Meulaboh Branch, West Aceh, in responding to the challenges of the unique and diverse local market. The marketing mix, consisting of product, price, place, and promotion, is a strategic framework for expanding market share and maintaining the company's competitiveness. Adjustment of financing products such as sharia-based two-wheeled vehicle financing and price flexibility based on local purchasing power shows relevance to local needs. Service distribution is optimized by placing offices in strategic locations and collaborating with local partners. Promotion strategies are carried out offline through community events and exhibitions, and online through social media and the Adiraku application. A descriptive narrative research method is used with interpretive data analysis based on documents and observations. The results of the study indicate that the implementation of a marketing mix that is adaptive to local culture and characteristics has succeeded in increasing brand awareness and customer loyalty at PT Adira Finance, Meulaboh Branch. This study emphasizes the importance of understanding the local market for the success of a marketing strategy.